THE MAIN FACTORS THAT CONTRIBUTE TO THE SHARP DAMAGE TO THE ECOLOGICAL ENVIRONMENT OF CITIES (Conferencea, 2023)
An increase in the number of inhabitants, an increase in the networks of industrial and manufacturing enterprises as the need for people increases, leads to a sharp increase in car-vehicles.These factors, along with the satisfaction of human needs, the development of their lives, lead to severe damage to the ecological environment of cities.